Preparation method of lithium nickel cobalt aluminate material
By adding lithium source and surface coating technology in step by step, the problems of insufficient stability and poor circulation performance of nickel-cobalt lithium aluminate materials in the high-nickel synthesis process are solved, and the stability and circulation performance of the material are improved.
Patent Information
- Application Number
- CN202311635087.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-06-03
AI Technical Summary
Nickel-cobalt lithium aluminate materials have problems such as insufficient stability, poor circulation performance and fast capacity attenuation during high-nickel synthesis.
Sintering is performed by adding lithium sources in step by step to reduce the content of alkaline substances, and surface coating is carried out by coating agents such as boric acid or alumina to improve the conductivity and structural stability of the material.
It improves the stability and circulation performance of nickel-cobalt lithium aluminate materials, delays capacity attenuation, and is suitable for the preparation of high-nickel-nickel-cobalt lithium aluminate materials.
Smart Images

Figure CN120089692A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and particularly relates to a preparation method of lithium nickel cobalt aluminate material. Background Art
[0002] In recent years, secondary batteries represented by lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the increasingly wide application range of secondary batteries, higher requirements are also put forward for their performance.
[0003] The positive electrode materials of lithium-ion batteries are mainly divided into three types: lithium iron phosphate, lithium manganate, and ternary materials. Among them, ternary materials have received wide attention due to their advantages such as high capacity, long life, and relatively low cost. The common ternary materials are lithium nickel cobalt aluminate (NCA) and lithium nickel cobalt manganate (NCM). Among them, the production barrier of lithium nickel cobalt aluminate is relatively high, and the production process requires stricter control. Moreover, in order to increase the energy density, the field hopes to synthesize high-nickel lithium nickel cobalt aluminate. However, affected by the defects in its synthesis process, it is prone to problems such as insufficient material stability, poor cycle performance when used in batteries, and rapid capacity decay. Summary of the Invention
[0004] The purpose of the present invention is to provide a preparation method of lithium nickel cobalt aluminate material. By applying this preparation method, it helps to improve the stability and long cycle performance of lithium nickel cobalt aluminate material, and also has the advantages of easy implementation and large-scale preparation, and has good application prospects.
[0005] Therefore, in the first aspect, the present invention provides a preparation method of lithium nickel cobalt aluminate material, which includes: mixing a ternary precursor with a first lithium source and performing a first sintering to obtain a first lithiated product; after coating the first lithiated product, mixing it with a second lithium source and performing a second sintering to obtain the lithium nickel cobalt aluminate material.
[0006] By adding the lithium source step by step, it is possible to reduce the content of basic substances such as lithium hydroxide and lithium carbonate in the product obtained after sintering, and avoid the gel phenomenon in the subsequent slurry preparation and coating processes due to excessive basic substances in the finished product; and by the way of adding the lithium source step by step, the lithium distribution in the material can be made uniform, which is beneficial to the conductivity and stability of the material.
[0007] In some embodiments, the coating is performed using at least one coating agent selected from the following group: boric acid, alumina.
[0008] In some embodiments, the molar amount of the coating agent is 0.03% - 0.1% of the first lithiated product.
[0009] In some embodiments, before mixing the ternary precursor with the first lithium source, the following pretreatment is performed on the ternary precursor: mixing the ternary precursor with a first dopant and performing pre-sintering. In some embodiments, the first dopant includes at least one selected from the group consisting of: a metal element, alloy, metal oxide, or metal fluoride containing Al, Mg, Ti, W, or Zr.
[0010] In some embodiments, the molar ratio of the ternary precursor to the first dopant is 1:0.003 to 1:0.03.
[0011] In some embodiments, the temperature condition for the pre-sintering is 450 to 600 °C; the time for the pre-sintering is 3 to 8 h.
[0012] In some embodiments, the ternary precursor is mixed with a second dopant and the first lithium source and subjected to first sintering. In some embodiments, the second dopant includes at least one selected from the group consisting of: a metal element, alloy, metal oxide, or metal fluoride containing Al, Mg, Ti, W, or Zr.
[0013] In some embodiments, the molar ratio of the ternary precursor to the second dopant is 1:0.003 to 1:0.03.
[0014] In some embodiments, the temperature of the first sintering is 710 to 950 °C; the time of the first sintering is 4 to 8 h.
[0015] In some embodiments, before mixing the ternary precursor with the first lithium source, the following pretreatment is performed on the ternary precursor: mixing the ternary precursor with a first dopant and performing pre-sintering; and, mixing the pre-sintered ternary precursor with a second dopant and the first lithium source and performing first sintering.
[0016] In some embodiments, the temperature of the second sintering is 710 to 950 °C; the time of the second sintering is 4 to 8 h.
[0017] In some embodiments, in the ternary precursor, the molar ratios of nickel, cobalt, and aluminum are x, y, and z respectively, where 0.8 ≤ x ≤ 0.9, 0.05 ≤ y ≤ 0.15, and 0 < z ≤ 0.05.
[0018] In some embodiments, the first lithium source and the second lithium source each independently include at least one selected from the group consisting of: lithium hydroxide or its hydrate, lithium lactate, lithium nitrate, and lithium oxalate.
[0019] In some embodiments, the molar ratio of lithium element in the first lithium source to the second lithium source is 1:0.94 to 1:1.16.
[0020] In some embodiments, the molar ratio of the sum of lithium elements in the first lithium source and the second lithium source to the sum of nickel, cobalt, and aluminum elements in the ternary precursor is 0.97:1 to 1.08:1.
[0021] In a second aspect of the present invention, there is provided a lithium nickel cobalt aluminate material prepared by the preparation method provided in the first aspect of the present invention.
[0022] In some embodiments, the lithium nickel cobalt aluminate material is a high-nickel lithium nickel cobalt aluminate material.
[0023] In a third aspect of the present invention, there is provided a positive electrode sheet, which includes a current collector and a positive electrode material layer provided on at least one surface of the current collector, and the positive electrode material layer includes the lithium nickel cobalt aluminate material prepared in the first aspect of the present invention.
[0024] In a fourth aspect of the present invention, there is provided a battery, which includes the positive electrode sheet provided in the third aspect of the present invention.
[0025] In some embodiments, the battery is a secondary battery. For example, it can be a lithium ion battery.
[0026] The above description is only an overview of the technical solution of the present invention. In order to be able to understand the technical means of the present invention more clearly, it can be implemented according to the content of the specification. And in order to make the above and other purposes, features and advantages of the present invention more obvious and understandable, the following specific embodiments of the present invention are listed. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] By reading the following detailed description of the preferred embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of showing the preferred embodiments and are not considered to be a limitation of the present invention. In the drawings:
[0028] Figure 1 : SEM image of the lithium nickel cobalt aluminate material prepared according to Example 1 provided by the present invention;
[0029] Figure 2 : SEM image of the lithium nickel cobalt aluminate material prepared according to Example 2 provided by the present invention;
[0030] Figure 3 : SEM image of the lithium nickel cobalt aluminate material prepared according to Example 3 provided by the present invention;
[0031] Figure 4 : SEM image of the lithium nickel cobalt aluminate material prepared in Comparative Example 1;
[0032] Figure 5:Cyclic capacity test results of the lithium nickel cobalt aluminate material prepared according to the specific embodiments provided by the present invention. Specific embodiments
[0033] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure can be more thoroughly understood and the scope of the present disclosure can be fully conveyed to those skilled in the art.
[0034] In the prior art, the preparation method of lithium nickel cobalt aluminate materials is still not perfect. For example, it is usually prepared according to the following method: a lithium source, a precursor, and a dopant are uniformly mixed by high speed and then prepared by one-time high-temperature sintering. When prepared by this method, it is easy to cause insufficient stability of the product. Moreover, for high-nickel lithium nickel cobalt aluminate materials, due to defects in the preparation method, problems such as insufficient material stability, poor cyclic performance when used in batteries, and rapid capacity decay are more likely to occur.
[0035] Therefore, an embodiment of the present invention provides a method for preparing a lithium nickel cobalt aluminate material, which includes: mixing a ternary precursor with a first lithium source and performing a first sintering to prepare a first lithiated product; after coating the first lithiated product, mixing it with a second lithium source and performing a second sintering to prepare the lithium nickel cobalt aluminate material.
[0036] By adding the lithium source in steps, the content of alkaline substances such as lithium hydroxide and lithium carbonate in the product obtained after sintering can be reduced, avoiding gel phenomena in the subsequent slurry preparation and coating processes due to excessive alkaline substances in the finished product; and by adding the lithium source in steps, the lithium distribution in the material can be made uniform, which is beneficial to the conductivity and stability of the material.
[0037] In some embodiments, the coating is performed using at least one coating agent selected from the group consisting of boric acid and alumina.
[0038] By uniformly coating the material surface, the occurrence of side reactions between the material and the electrolyte can be inhibited to a certain extent, and the stability of the material structure can be improved. In some embodiments, the ternary material prepared by boric acid coating can improve the rate performance of the material, and at the same time boric acid can react with the residual alkali in the material to improve the cyclic stability of the material. In some embodiments, the ternary material prepared by alumina coating can form a protective oxide film at the interface between the electrode and the electrolyte, inhibit the occurrence of side reactions, and reduce the capacity decay problem caused by Li + loss.
[0039] In some embodiments, the step of coating the first lithiated product includes: mixing the first lithiated product with water, then slowly adding a coating agent under stirring conditions, and then successively performing filtration and drying to obtain the coated first lithiated product, which is used in subsequent steps. In some embodiments, the mixing can be carried out according to a mass ratio of the first lithiated product to water of 1:1 to 2. In some embodiments, the time for slowly adding the coating agent under stirring conditions is 5 to 10 min. In some embodiments, the drying conditions for the coated product can be vacuum drying at 120 to 140 °C for 4 to 8 h. In some embodiments, the molar dosage of the coating agent is 0.03% to 0.1% of the first lithiated product; for example, it can be about 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc.
[0040] In some embodiments, before mixing the ternary precursor with the first lithium source, the following pretreatment is performed on the ternary precursor: mixing the ternary precursor with a first dopant and performing pre-sintering. In some embodiments, the first dopant includes at least one selected from the group consisting of a metal element, alloy, metal oxide, or metal fluoride containing Al, Mg, Ti, W, or Zr.
[0041] Pre-sintering the precursor and the doping element helps to reduce the degree of atomic mixing and can also play a certain role in impurity removal. When doped with elements such as Al, Mg, and Zr, it can not only reduce the degree of cation mixing in the ternary material but also be beneficial to improving the electrochemical cycling performance and thermal stability.
[0042] In some embodiments, the molar ratio of the ternary precursor to the first dopant is 1:0.003 to 1:0.03.
[0043] In some embodiments, the temperature condition for the pre-sintering is 450 to 600 °C; for example, it can be about 450 °C, 500 °C, 550 °C, 600 °C, etc. In some embodiments, the pre-sintering time is 3 to 8 h; for example, it can be about 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, etc. In some embodiments, the pre-sintering is carried out under an oxygen atmosphere condition, such as a 95% oxygen atmosphere.
[0044] In some embodiments, the ternary precursor is mixed with a second dopant and a first lithium source and subjected to first sintering. In some embodiments, the second dopant includes at least one selected from the group consisting of a metal element, alloy, metal oxide, or metal fluoride containing Al, Mg, Ti, W, or Zr.
[0045] Doping with a second dopant helps to further improve the properties of the material. For example, doping with Mg and Ti elements is beneficial to reducing the cation mixing degree in the ternary material and improving the electrochemical cycling performance and thermal stability. F element doping can endow the chemical bonds in the material with higher bond energy, reduce the corrosion of the material by hydrofluoric acid, reduce the dissolution of Co. At the same time, F element doping is also beneficial to reducing the electrolyte / electrode interface resistance, thereby improving the cycling performance. W element doping can form a layer of Li 2 WO 4 or Li x WO 3 on the material surface, which is a good Li + conductor and is beneficial to promoting Li + diffusion, thereby reducing electrochemical polarization and improving the rate performance; in addition, W element doping can also improve the corrosion resistance of the material and improve the cycling performance of the material.
[0046] In some embodiments, the molar ratio of the ternary precursor to the second dopant is 1:0.003 to 1:0.03.
[0047] In some embodiments, the ternary precursor, the first dopant and the second dopant are mixed and pre-sintered, and the pre-sintered ternary precursor is mixed with the first lithium source and subjected to the first sintering.
[0048] In some embodiments, the ternary precursor is mixed with the first dopant and pre-sintered, and the pre-sintered ternary precursor is mixed with the second dopant and the first lithium source and subjected to the first sintering.
[0049] In some embodiments, the ternary precursor, the first dopant, the second dopant and the first lithium source are mixed and subjected to the first sintering.
[0050] In some embodiments, the first dopant and the second dopant may be the same or different. Preferably, the first dopant and the second dopant are different.
[0051] In some embodiments, the temperature of the first sintering is 710 - 950 °C; for example, it can be about 710 °C, 750 °C, 800 °C, 850 °C, 900 °C, 950 °C, etc.; the time of the first sintering is 4 - 8 h; for example, it can be about 4 h, 5 h, 6 h, 7 h, 8 h, etc. In some embodiments, the first sintering is carried out under an oxygen atmosphere condition, such as 95% oxygen atmosphere.
[0052] By means of step-by-step doping, gradient doping can be formed in the material, giving full play to the role of the dopant. This helps to avoid the antagonistic effect caused by the one-time addition of the dopant in the existing process, that is, each doping element cannot fully play its respective role, affecting the stability of the material morphology and crystal structure, and ultimately leading to poor cycling and capacity drop phenomena.
[0053] In some embodiments, before the second sintering, it is necessary to keep the temperature at 400 - 550 °C for 2 - 4 h to remove the water vapor and / or carbon dioxide in the air combined by the first lithiation product during the coating process.
[0054] In some embodiments, the temperature of the second sintering is 710 - 950 °C; for example, it can be about 710 °C, 750 °C, 800 °C, 850 °C, 900 °C, 950 °C, etc.; the time of the second sintering is 4 - 8 h; for example, it can be about 4 h, 5 h, 6 h, 7 h, 8 h, etc. In some examples, the second sintering is carried out under an oxygen atmosphere condition, such as a 95% oxygen atmosphere.
[0055] In some embodiments, after the second sintering, the following optional steps are further included: crushing, sieving, and demagnetization.
[0056] In some embodiments, in the ternary precursor, the molar ratios of nickel, cobalt, and aluminum are x, y, and z respectively, where 0.8 ≤ x ≤ 0.9, 0.05 ≤ y ≤ 0.15, and 0 < z ≤ 0.05. In some examples, the range of x can be: 0.80 ≤ x ≤ 0.9, 0.81 ≤ x ≤ 0.9, 0.82 ≤ x ≤ 0.9, 0.83 ≤ x ≤ 0.9, 0.84 ≤ x ≤ 0.9, 0.85 ≤ x ≤ 0.9, 0.86 ≤ x ≤ 0.9, 0.87 ≤ x ≤ 0.9, 0.88 ≤ x ≤ 0.9, 0.89 ≤ x ≤ 0.9, etc.
[0057] The preparation method provided by the embodiments of the present invention is suitable for lithium nickel cobalt aluminate materials with different nickel contents, especially suitable for high-nickel lithium nickel cobalt aluminate materials. Using the method of the embodiments of the present invention to prepare high-nickel lithium nickel cobalt aluminate materials, good technical effects can still be achieved in terms of stability, cycling performance, and capacity retention.
[0058] In some embodiments, the first lithium source and the second lithium source each independently include at least one selected from the following group: lithium hydroxide or its hydrate, lithium lactate, lithium nitrate, lithium oxalate.
[0059] In some embodiments, the molar ratio of lithium elements in the first lithium source and the second lithium source is 1:0.94 - 1:1.16.
[0060] In some embodiments, the molar ratio of the sum of lithium elements in the first lithium source and the second lithium source to the sum of nickel, cobalt, and aluminum elements in the ternary precursor is 0.97:1 to 1.08:1.
[0061] In some embodiments, the ternary precursor can be prepared by the following method: providing a mixed solution containing soluble salts of nickel, cobalt, and aluminum, and subjecting the mixed solution to a precipitation reaction; then successively washing, filtering, and drying to obtain the ternary precursor. As an example, soluble salts of nickel can include nickel acetate, nickel chloride, nickel nitrate, or nickel sulfate, etc.; soluble salts of cobalt can include cobalt chloride, cobalt sulfate, or cobalt nitrate, etc.; soluble salts of aluminum can include aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum trifluoromethanesulfonate, aluminum acetate, aluminum ethoxide, or aluminum hydroxyoxalate, etc.
[0062] In some embodiments, the step of performing the precipitation reaction includes: adding an alkali solution (such as sodium hydroxide) and ammonia water (such as making the NH 3 content in the system 3 - 5 g / L) to the reaction system, and controlling the pH value of the reaction system to be alkaline (such as 10 - 12), and performing the precipitation reaction under stirring conditions. For example, during the precipitation reaction, the pH value and ammonia content can be adjusted according to the particle size of the generated crystal nuclei, so as to adjust the crystal nucleus particle size, and stop feeding after the crystal nucleus particle size reaches a certain value. In some embodiments, the precipitation reaction is carried out under a protective atmosphere (such as nitrogen, inert gas, etc.).
[0063] In some embodiments, the drying step may include: drying the filtered material at a temperature of 150 - 200 °C for 8 - 12 h under a protective atmosphere (such as nitrogen, inert gas, etc.) to obtain the ternary precursor.
[0064] Some embodiments of the present invention provide a lithium nickel cobalt aluminate material, which is prepared according to the preparation method provided in the embodiments of the present invention.
[0065] In some embodiments, the lithium nickel cobalt aluminate material is a high-nickel lithium nickel cobalt aluminate material.
[0066] Some embodiments of the present invention provide a positive electrode plate, which includes a current collector and a positive electrode material layer provided on at least one surface of the current collector, and the positive electrode material layer includes the lithium nickel cobalt aluminate material prepared in the embodiments of the present invention.
[0067] Some embodiments of the present invention provide a battery, which includes the positive electrode plate provided in the embodiments of the present invention.
[0068] In some embodiments, the battery is a secondary battery. For example, it can be a lithium-ion battery.
[0069] Some embodiments of the present invention provide an electrical device, which includes the battery provided by the embodiments of the present invention.
[0070] Example 1
[0071] (I) Preparation of ternary precursor
[0072] (1) Prepare a 1 mol / L nickel-cobalt-aluminum mixed salt solution using nickel nitrate as the nickel salt, cobalt sulfate as the cobalt salt, and aluminum nitrate as the aluminum salt, where the molar ratio of nickel, cobalt, and aluminum is 88:9:3; prepare a 40% mass concentration NaOH solution and a 25% mass concentration ammonia water solution.
[0073] (2) Add 20 L of the above nickel-cobalt-aluminum mixed salt solution to a closed synthesis reactor, and at the same time add a certain amount of ammonia water and NaOH solution to make the NH 3 content 4 g / L and the pH value 12. Control the temperature of the reactor at 65 °C, introduce nitrogen to displace the air in the reactor, and under the stirring condition of a rotation speed of 400 rpm, add the above nickel-cobalt-aluminum mixed salt solution, NaOH solution, and ammonia water solution to the reactor for starting the reaction in a certain proportion, where the flow rate of the nickel-cobalt-aluminum mixed salt solution is controlled at 1 L / h, the pH value is 12, and the NH 3 content is 4 g / L, and nitrogen is introduced throughout the reaction for protection;
[0074] (3) When the crystal nucleus particle size D50 in the reactor grows to 10 μm, finely adjust the pH value to stably maintain the particle size D50 in the reactor at 5 - 10 μm. At this time, the product is a qualified slurry, which overflows into the aging kettle for collection;
[0075] (4) After aging for 2 h, wash with pure water using a centrifuge, wash according to 11 kg of pure water per 1 kg of product, and the pH of the washing water after washing is < 8. After washing and dehydrating, then dry the obtained material in an oven at 150 °C to obtain the ternary precursor; it is used for the subsequent preparation of this example.
[0076] (II) Preparation of lithium nickel cobalt aluminum oxide material
[0077] (1) Pass the ternary precursor through a 200-mesh sieve and then mix it with nanoscale zirconia as the first dopant in a high-speed mixer for 1 h. The molar ratio of the ternary precursor to the first dopant is 1:0.005; then place the uniformly mixed material in a crucible, put it into a sintering furnace, introduce 95% oxygen, sinter at 550 °C for 8 h, and naturally cool down after sintering to obtain the pretreated ternary precursor;
[0078] (2) The pretreated ternary precursor is mechanically ground and crushed, screened through a 200-mesh sieve, and then mixed with lithium hydroxide as the first lithium source and magnesium fluoride as the second dopant in a high-speed mixer for 1 h. The molar ratio of the pretreated ternary precursor, lithium element in the first lithium source, and the second dopant is 1:0.5:0.005. Then the uniformly mixed materials are filled in a crucible, placed in a sintering furnace, 95% oxygen is introduced, and sintered at 800 °C for 8 h. After sintering, it is naturally cooled to obtain the first lithiated product.
[0079] (3) The first lithiated product is mechanically ground and crushed, screened through a 300-mesh sieve, and then mixed with pure water at a ratio of 1:1, and stirred in a stirrer at a speed of 500 r / min for 5 min. During the stirring process, alumina powder as the coating agent is slowly added, and the molar dosage of the coating agent is 0.03% of the first lithiated product. After stirring, it is vacuum filtered to remove most of the moisture, and then the semi-wet powder is transferred to an oven at 120 °C and vacuum dried for 6 h to obtain the coated first lithiated product.
[0080] (4) After the coated first lithiated product is screened through a 300-mesh sieve, it is mixed with lithium hydroxide as the second lithium source in a high-speed mixer for 1 h. The molar ratio of the lithium element of the coated first lithiated product to the second lithium source is 1:0.53. Then the uniformly mixed materials are filled in a crucible, placed in a sintering furnace, 95% oxygen is introduced, held at 400 °C for 4 h, and then sintered at 750 °C for 8 h. After sintering, it is naturally cooled, and then mechanically ground and crushed, screened through a 300-mesh sieve, and demagnetized in sequence to prepare lithium nickel cobalt aluminate material. Its microscopic morphology diagram (SEM diagram) is as Figure 1 shown.
[0081] Test:
[0082] The button cell is prepared according to the following steps: The obtained cathode material is mixed with conductive agent KS-6, conductive carbon black, and PVDF in a mass ratio of 90:1.5:1.5:7, and N-methylpyrrolidone (NMP) solution is added. The mass ratio of PVDF:NMP is 0.03:1. The above substances are placed in a high-speed mixer and mixed evenly to obtain a black slurry. The slurry is evenly coated on the aluminum foil, and then the aluminum foil is transferred to a blast drying oven for heating. The heating temperature is 105 °C, and the heating time is 15 - 20 min until the NMP is completely volatilized. The coated material is roll-pressed and sliced to obtain the cathode sheet. The cathode sheet is transferred to a vacuum oven and continuously dried at 120 °C for more than 4 h. After complete drying, it is weighed and the mass of the electrode sheet is recorded, and then transferred to a glove box for button cell assembly. It is assembled in the order of the positive electrode shell, positive electrode sheet, PE separator, lithium sheet, gasket, spring sheet, and negative electrode shell. An appropriate amount of electrolyte is dropped inside the battery to ensure that the internal structure can be completely infiltrated. The electrolyte manufacturer is Shinzo, and the model is LBC305-01.
[0083] The coin-type battery was tested: The coin-type battery was tested using a Neware test cabinet at a constant temperature of 25 °C. First, the test current was calculated based on the mass of the active material in the positive electrode sheet. The coin-type battery was subjected to 0.2C charge and discharge tests for 2 cycles, then 0.5C charge and discharge tests for 3 cycles, and then 1C charge and discharge tests for 100 cycles. The charging cut-off voltage was 4.3V, and the discharging cut-off voltage was 3.0V. From the test results, the electrical property differences of the materials could be known. The calculation formula for the capacity retention rate of the material after 100 cycles at 1C is:
[0084] Capacity retention rate = Discharge specific capacity at the 100th cycle at 1C / Discharge specific capacity at the first cycle at 1C * 100%
[0085] The results are as Figure 5 shown. The capacity at 1C is 186.8 mAh / g, and the capacity retention rate after 100 cycles at 1C is 93.4%.
[0086] Example 2
[0087] Except for the following differences, the preparation and testing were carried out in the same method as in Example 1:
[0088] The first dopant was magnesium oxide;
[0089] The second dopant was titanium dioxide;
[0090] The first lithium source was lithium hydroxide monohydrate;
[0091] The second lithium source was lithium hydroxide monohydrate, and the molar ratio of the lithium element in the coated first lithiated product to the second lithium source was 1:0.55.
[0092] The microscopic morphology diagram of the lithium nickel cobalt aluminate material prepared in Example 2 is as Figure 2 shown; the test results of the cycle capacity are as Figure 5 shown. The capacity at 1C is 184 mAh / g, and the capacity retention rate after 100 cycles at 1C is 94.6%.
[0093] Example 3
[0094] Except for the following differences, the preparation and testing were carried out in the same method as in Example 1:
[0095] The first dopant was aluminum oxide, and the molar ratio of the ternary precursor to the first dopant was 1:0.007;
[0096] The second dopant was tungsten trioxide;
[0097] The first lithium source was lithium lactate;
[0098] The coating agent uses boric acid powder, and the molar dosage of the coating agent is 0.1% of the first lithiated product;
[0099] The second lithium source uses lithium lactate, and the molar ratio of the lithium element of the coated first lithiated product to the second lithium source is 1:0.55.
[0100] The lithium nickel cobalt aluminum oxide material prepared in Example 3 has a microscopic morphology as shown in Figure 3 shown; the test results of the cycle capacity are as shown in Figure 5 shown, the capacity at 1C is 183.5 mAh / g, and the capacity retention rate after 100 cycles at 1C is 93.6%
[0101] Examples 4 - 5
[0102] Except for the differences shown in Table 1, the preparation and testing were carried out according to the same steps as in Example 1, and the test results are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] Comparative Example 1
[0107] (I) Preparation of ternary precursor
[0108] Same as Example 1.
[0109] (II) Preparation of lithium nickel cobalt aluminum oxide material
[0110] After passing the ternary precursor through a 200 - mesh sieve, it was mixed with lithium hydroxide in a high - speed mixer for 1 h. The mass ratio of the lithium element in the ternary precursor to that in lithium hydroxide was 1:1.03; then the uniformly mixed material was placed in a crucible, put into a sintering furnace, 95% oxygen was introduced, and sintered at 750 °C for 8 h; after sintering, it was naturally cooled, and then successively subjected to mechanical grinding, passing through a 300 - mesh sieve, and demagnetization to obtain the lithium nickel cobalt aluminum oxide material, whose microscopic morphology is as shown in Figure 4 shown.
[0111] Tested according to the same method as in Example 1, the test results of the cycle capacity are as shown in Figure 5 shown, the capacity at 1C is 168.8 mAh / g, and the capacity retention rate after 100 cycles at 1C is 82.3%.
[0112] Comparative Example 2
[0113] Except for the following differences, the preparation and testing were carried out according to the same method as in Comparative Example 1:
[0114] After passing the ternary precursor through a 200-mesh sieve, it is mixed with lithium hydroxide, nanoscale zirconia, and magnesium fluoride in a high-speed mixer for 1 h. The molar ratio of the ternary precursor, lithium element in lithium hydroxide, zirconia, and magnesium fluoride is 1:1.03:0.005:0.005.
[0115] The lithium nickel cobalt aluminum oxide material is prepared, and its capacity in the first cycle at 1C is 172.2 mAh / g, and the capacity retention rate after 100 cycles at 1C is 88.6%.
[0116] Comparing Examples 1-3 with Examples 4-5 shows that: step-by-step doping can give full play to the role of doping elements more than one-time doping, reduce the antagonistic effect between doping substances, improve the material capacity, and improve the comprehensive performance.
[0117] Comparative Example 1 shows that: directly sintering the ternary precursor and the lithium source at high temperature, the NCA material without stepwise lithium addition, doping, and surface coating modification cannot reach the expected initial capacity, and the capacity decays too fast, and the cycling performance is poor.
[0118] Comparative Example 2 shows that: directly sintering the ternary precursor, the lithium source, and the doping substances at one time, although the capacity is relatively increased and the capacity decay becomes slower, the improvement effect is limited and the requirements cannot be met.
[0119] Appendix Figures 1-4 Explanation: For the NCA material with stepwise lithium addition, doping, and surface coating, its appearance and morphology are greatly improved, the particle size is effectively controlled, which is beneficial to increasing the specific surface area of the material and accelerating charge transfer, thereby improving the comprehensive performance of the material. For the unmodified NCA material, there are some irregular particles, and the particles are prone to agglomeration, which affects its electrochemical performance, resulting in low material capacity and fast decay.
[0120] Appendix Figure 5 Explanation: At the same charge-discharge voltage of 4.3 - 3V, cycling 100 weeks at 1C, the capacity decay rate of the modified material drops significantly, and the material capacity increases, which can improve the electrochemical performance of the material.
[0121] As mentioned above, the above are only the preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.
Claims
1. A preparation method of lithium nickel cobalt aluminate material, characterized in that, comprising: mixing a ternary precursor with a first lithium source and performing a first sintering to obtain a first lithiated product; after coating the first lithiated product, mixing it with a second lithium source and performing a second sintering to obtain the lithium nickel cobalt aluminate material.
2. The preparation method according to claim 1, characterized in that, the coating is carried out using at least one coating agent selected from the group consisting of boric acid and alumina; preferably, the molar amount of the coating agent is 0.03% - 0.1% of the first lithiated product.
3. The preparation method according to claim 1, characterized in that, before mixing the ternary precursor with the first lithium source, the ternary precursor is subjected to the following pretreatment: mixing the ternary precursor with a first dopant and performing a pre-sintering; and / or, mixing the ternary precursor with a second dopant and the first lithium source and performing a first sintering.
4. The preparation method according to claim 3, characterized in that, the first dopant includes at least one selected from the group consisting of metallic elements, alloys, metal oxides or metal fluorides containing Al, Mg, Ti, W or Zr; preferably, the second dopant includes at least one selected from the group consisting of metallic elements, alloys, metal oxides or metal fluorides containing Al, Mg, Ti, W or Zr.
5. The preparation method according to claim 3, characterized in that, the molar ratio of the ternary precursor to the first dopant is 1:0.003 - 1:0.03; preferably, the molar ratio of the ternary precursor to the second dopant is 1:0.003 - 1:0.
03.
6. The preparation method according to any one of claims 1 - 5, characterized in that, in the ternary precursor, the molar ratios of nickel, cobalt and aluminum are x, y and z respectively, where 0.8 ≤ x ≤ 0.9, 0.05 ≤ y ≤ 0.15, 0 < z ≤ 0.
05.
7. The preparation method according to any one of claims 1 - 5, characterized in that, each of the first lithium source and the second lithium source independently includes at least one selected from the group consisting of lithium hydroxide or its hydrate, lithium lactate, lithium nitrate and lithium oxalate; preferably, the molar ratio of lithium elements in the first lithium source and the second lithium source is 1:0.94 - 1:1.16; preferably, the molar ratio of the sum of lithium elements in the first lithium source and the second lithium source to the sum of nickel, cobalt and aluminum elements in the ternary precursor is 0.97:1 - 1.08:
1.
8. A lithium nickel cobalt aluminate material, characterized in that, the lithium nickel cobalt aluminate material is prepared according to the preparation method described in any one of claims 1 - 7.
9. A positive electrode plate, characterized in that, comprising a current collector and a positive electrode material layer provided on at least one surface of the current collector, and the positive electrode material layer includes the lithium nickel cobalt aluminate material prepared according to the preparation method described in any one of claims 1 - 7.
10. A battery, characterized in that, comprising the positive electrode plate described in claim 9.